Learning the Basics of Artificial Intelligence in High School Computer Science Classes - Osadchа, Kateryna; Osadchа, Maryna (Educological discourse, 2024)
The article investigates the issue of generative AI technologies in high school computer science classes. The purpose of the study was to develop a methodology for studying AI in high school. For this purpose, a comprehensive analytical approach was applied, including such methods as analysis of regulatory documents, review of scientific literature and Internet sources, synthesis and interpretation of data, and critical analysis. The authors analyzed computer science curricula for grades 10 and 11, standard and advanced level textbooks, as well as scientific publications by Ukrainian and foreign scholars. Findings indicate that artificial intelligence is not addressed as a standalone curriculum topic but is integrated into broader modern information technology topics, and textbooks primarily provide a general introduction to AI concepts, basic principles, and applications rather than emphasizing practical use. Based on the analysis of scientific research, it is concluded that there is insufficient coverage of the problems of teaching artificial intelligence technologies in high school computer science classes, in particular, there are no clear indications of the content, plan, sequence of studying artificial intelligence technologies, etc. In general, there is no consistent program for studying artificial intelligence in high school. With this in mind, the authors analyzed English-language resources for teaching artificial intelligence. The study of these resources, in turn, allowed authors to develop methodological recommendations for the study of artificial intelligence technologies in computer science classes in grades 10 and 11. The methodological recommendations are presented in the article in two thematic plans: one for grade 10 and one for grade 11, each containing a list of topics (six for grade 10 and ten for grade 11) and links to relevant instructional resources. The methodology is a comprehensive approach designed for two years of study and aimed at gradually deepening students' knowledge and skills. It allows students not only to gain in-depth theoretical knowledge of artificial intelligence, but also to develop practical skills in its use, and promotes ethical understanding and critical thinking about artificial intelligence technologies.